A new glioblastoma cell trap for implantation after surgical resection. (15th January 2019) - Autier, Lila; Clavreul, Anne; Cacicedo, Maximiliano L.; Franconi, Florence; Sindji, Laurence; Rousseau, Audrey; Perrot, Rodolphe; Montero-Menei, Claudia N.; Castro, Guillermo R.; Menei, Philippe
Graphical abstract: Abstract: Glioblastoma (GB) is a highly infiltrative tumor, recurring, in 90% of cases, within a few centimeters of the surgical resection cavity, even with adjuvant chemo/radiotherapy. Residual GB cells left in the margins or infiltrating the brain parenchyma shelter behind the extremely fragile and sensitive brain tissue and may favor recurrence. Tools for eliminating these cells without damaging the brain microenvironment are urgently required. We propose a strategy involving the implantation, into the tumor bed after resection, of a scaffold to concentrate and trap these cells, to facilitate their destruction by targeted therapies, such as stereotactic radiosurgery. We used bacterial cellulose (BC), an easily synthesized and modifiable random nanofibrous biomaterial, to make the trap. We showed that the structure of BC membranes was ideal for trapping tumor cells and that BC implants were biocompatible with brain parenchyma. We also demonstrated the visibility of BC on magnetic resonance imaging, making it possible to follow its fate in clinical situations and to define the target volume for stereotactic radiosurgery more precisely. Furthermore, BC membranes can be loaded with chemoattractants, which were released and attracted tumor cells in vitro . This is of particular interest for trapping GB cells infiltrating tissues within a few centimeters of the resection cavity. Our data suggest that BC membranes could be a scaffold of choice for implantation after surgical resection to trap residual GB cells. Statement of Significance: Glioblastoma is a highly infiltrative tumor, recurring, in 90% of cases, within a few centimeters of the surgical resection cavity, even with adjuvant chemo/radiotherapy. Residual tumor cells left in the margins or infiltrating the brain parenchyma shelter behind the extremely fragile and sensitive brain tissue and contribute to the risk of recurrence. Finding tools to eliminate these cells without damaging the brain microenvironment is a real challenge. We propose a strategy involving the implantation, into the walls of the surgical resection cavity, of a scaffold to concentrate and trap the residual tumor cells, to facilitate their destruction by targeted therapies, such as stereotactic radiosurgery.